Manajemen Mutu Pembelajaran dalam Meningkatkan Kesiapan Siswa SMA Swasta UISU Medan untuk Memasuki Perguruan Tinggi - Putri Ai Nurmuslimah; Nurhaizan Sembiring; Rabiatul Adawiyah (Lembaga Yasin AlSys, 2026)
Although learning quality management has received attention in a number of previous studies, studies that specifically discuss efforts to improve the readiness of students at SMA Swasta UISU Medan to enter higher education remain limited. This study aims to describe the implementation, planning, and execution of learning quality management in improving students’ readiness to enter higher education at SMA Swasta UISU Medan. This study used a qualitative approach with a case study design, utilizing primary and secondary data sources. Data were collected through observation, in-depth interviews, and documentation, then analyzed through the stages of data reduction, data display, and conclusion drawing, with data validity tested using triangulation techniques. The results showed that learning quality management had been implemented in a structured manner through aptitude and interest tests, periodic tryouts, and active problem-based learning. The planning of student readiness began in Grade XI and was developed further in Grade XII through content enrichment, examination simulations, and counseling guidance. Its implementation involved all school components synergistically. The conclusion of this study emphasizes that structured learning quality management involving all stakeholders has a positive impact on students’ readiness to enter higher education. The implications of this study include a theoretical contribution to enriching the literature on learning quality management as well as practical implications for educational institutions in preparing students to enter higher education. This study also opens opportunities for further research on the role of principals and teachers in building students’ self-confidence in decision-making.